2015
DOI: 10.1210/jc.2015-2923
|View full text |Cite
|
Sign up to set email alerts
|

Social Jetlag, Chronotype, and Cardiometabolic Risk

Abstract: Our findings suggest that a misalignment of sleep timing is associated with metabolic risk factors that predispose to diabetes and atherosclerotic cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
282
4
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(318 citation statements)
references
References 51 publications
22
282
4
10
Order By: Relevance
“…These changes were found to be independent of changes in sleep duration (Leproult et al, 2014). In a population-based study, evening chronotype, which is typically associated with a mild form of circadian misalignment, has been associated with metabolic syndrome (Yu et al, 2015), type 2 diabetes (Merikanto et al, 2013;Yu et al, 2015) and lower HDL cholesterol (Wong et al, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…These changes were found to be independent of changes in sleep duration (Leproult et al, 2014). In a population-based study, evening chronotype, which is typically associated with a mild form of circadian misalignment, has been associated with metabolic syndrome (Yu et al, 2015), type 2 diabetes (Merikanto et al, 2013;Yu et al, 2015) and lower HDL cholesterol (Wong et al, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, irregular eating patterns and reduced daylight exposure are also common lifestyles changes in the modern 24/7 society [6, 7]. There is convincing evidence that all these lifestyle changes contribute to circadian (see glossary) disturbances [8-10]. Recently, accumulating epidemiological evidence has indicated that circadian disturbances in the forms of shift work [11, 12], late meal timing [6], late chronotype [13, 14], social jet lag [15], and sleep loss [16] are associated with increased risks of T2D.…”
Section: Lifestyle Changes Relevant To Circadian Disturbances and mentioning
confidence: 99%
“…Although sleep disturbances are known to affect health and behavior, 6 we cannot presume a direct causal relationship between such outcomes and SJL, which appears mostly as a variable that characterizes the study samples. Thus, we chose to exclude studies that did not explicitly assess illness Levandovski et al 2011 29 Roenneberg et al 2012 21 Johnsen et al 2013 22 Kantermann et al 2013 27 Schimitt et al 2013 35 Haraszti et al 2014 40 Kantermann et al 2014 25 Miller et al 2015 44 Rutters et al 2014 28 Borisenkov et al 2015 32 Parsons et al 2015 35 Tavernier et al 2015 42 Wong et al 2015 26 Choi et al 2016 45 Kolomeichuk et al 2016 38 Polugrudov et al 2016 24 Sheaves et al 2016 30 Silva et al 2016 46 Yong states or behavioral outcomes. Furthermore, it is very likely that sleep deficit correlates with SJL.…”
Section: Excluded Studies and Terminologymentioning
confidence: 99%
“…Kantermann et al 25 found no association between SJL and metabolic risk parameters in male shift workers, which may be due to the small sample size. However, Parsons et al 23 found that individuals with higher SJL were more likely to meet the criteria for metabolic syndrome and Wong et al 26 found higher cardiometabolic risk markers associated with higher SJL in larger samples of both sexes. Regarding the risk of cardiovascular pathologies, a positive correlation between SJL and heart rate has been demonstrated.…”
Section: Summary Of Findingsmentioning
confidence: 99%